KUPU-KUPU (RHOPALOCERA) DI SEKITAR KAMPUS UNIVERSITAS PASIR PENGARAIAN KABUPATEN ROKAN HULU PROVINSI RIAU - Rodianti, Mala; Yolanda, Rofiza; Mubarrak, Jismi (Jurnal Ilmiah Mahasiswa FKIP Prodi Biologi, 2015)
Study about butterflies (Rhopalocera) around Pasir Pengaraian University campus Rokan hulu regency Riauprovince was conducted in August to December 2014 by using survey method with random sampling techniques.Samples collected by using insect net and cylindrical gauze on the campus gate, around the campus portal, around faculty of agriculture and around midwifery with 4 repetitions. Result showed 7 families, 16 genera and 24 species butterflies. Diversity index values was ranged from 2,19 to 2,48 and concluded in medium category